Multiple level spondylodiscitis with presacral abscess in spinal brucellosis: a rare presentation - Alexander, Lobo; Adukia, Sachin; Prajapati, Jignesh (International Journal of Medicine, 2017)
Importance: We report an unusual presentation of spinal brucellosis involving multilevel spondylodiscitis, prevertebral sacral abscess and isolation of Brucella using a low-yield test like blood culture. Timely identification helped in dispensing the appropriate antibiotic regimen.Observation:Detailed history against an endemic background may give clues to diagnosis of brucellosis. A middle aged farmer from rural India with exposure to cattle excreta presented with severe lower backache and asymmetric paraparesis. Examination revealed proximal lower limb weakness, sensory deficits over L1-L2 dermatomes, sensory level at L1 vertebral level and lumbosacral spinal tenderness with paravertebral muscle spasms. MRI spine with contrast showed multi-level infective spondylodiscitis with a prevertebral sacral abscess. Blood culture helped isolate Brucella melitensis after 8 days. Following this the antibiotic regimen was modified to a twelve month triple therapy with rifampicin, doxycycline and double strength cotrimoxazole.Conclusions and Relevance: Longstanding backache with fever in endemic areas should trigger a differential diagnosis of spinal brucellosis. Though newer diagnostic techniques like ELISA, MRI and agglutination tests are being increasingly used, isolation of Brucella on culture media is still a vital investigation. Diagnosis of brucellosis is vital owing to its potential treatability.